Методика управління економічною ефективністю реконструкції сільського житлового фонду в межах міст КНР - Шаоцин, Гао (Ways to Improve Construction Efficiency, 2014)
The method of management economic efficiency reconstruction "villages in the city", which consists of seven stages. This approach allows reasonably choose indicators to assess the cost-effectiveness, control housing reconstruction.